Comparison among different inertial-based algorithms for the automatic detection of temporal events in sprint tests: a preliminary study on elite athletes with intellectual impairment - Caporaso, T.; Palomba, A.; Grazioso, S.; Megna, A.; Panariello, D.; Perez, D.; Marchettoni, P.; di Gironimo, G.; Lanzotti, A. (2020 IEEE International Workshop on Metrology for Industry 4.0 & IoT, 2020)
A fast and objective evaluation of kinematic characteristics of an elite athlete's gesture is necessary for refining her/his performance. When the athlete has a reduced capacity and/or reliability of expression, as in the case of subjects with intellectual impairment, objective performance analyses are even more important. In this work, we present a preliminary study regarding performance analysis on sprint tests performed by elite athletes with intellectual impairment, wearing an inertial sensor at the bottom end of their vertebral column. In particular, we compare three different inertial-based algorithms for automatic detection of temporal events, in steady-state velocity phase, with respect to the benchmark values obtained through video analysis.